Strategic responses to global climate change: evidence from canadian oil companies - Araújo, Francisco Sávio Maurício (2018)
This work applies the climate change strategy model in order to understand how organizational characteristics, institutional pressures, and managerial perceptions of risks and opportunities affect the carbon strategies of large CO2 polluting firms in Canada. In order to achieve the main objectives, this paper proposes to identify the key clusters and their positioning in relation to corporate climate strategies and to investigate the role of stakeholders, main concerns, and problems faced by companies in the Canadian context. Canada is a leader resource-based economy built upon a fossil matrix and at the same time, a climate policy laggard with business participation confined to defensive lobbying activities. For these reasons, it is justified as an interesting analytical environment. This work is theoretically supported by resource-based, institutional, and stakeholder theories. The findings are based on a survey with 127 managers of oil & gas companies and 18 semi-structured interviews with key stakeholders of Canadian environment (Academics, NGOs, and government) which are sensitive to climate change issues. The survey data is performed through factorial analysis, structural equations modeling and clustering while the interviews were evaluated through content analysis of stakeholder´s speech in a quantitative-qualitative approach. The results show that companies undertake one of four different strategies ranging from a minimalist approach to the regulation shaper, pressure manager or greenhouse gas emission avoiders. This work contributes to an understanding of the importance of embedding climate change in a business model in Canadian oil and gas markets